A Closer Look at Communication Strategy: A Framework for the Term Communication Strategy - Widiarini Widiarini (Journal of Development Research, 2019)
Communication ability becomes main parameter of the successfulness of English language learners in learning English. However, communication ability can not be acquired instantly, English learners need more practices and also strategies in communication. In addition communication ability also influenced by some factors such as target language proficiency, learning and communicating contexts, task types, gender differences and learners’ personality. Driven by this condition, this paper is aimed to discuss theoretical framework about communication strategies and its development since firstly proposed by Tarone (1977). This paper is beneficial for English language practitioner and English language learners, ELT researcher as well.